Adverse Effects of CEO Family-to-Work Conflict on Firm Performance - Reina, Christopher S.; Peterson, Suzanne J.; Zhang, Zhen (Organization Science, 2017)
We examine whether chief executive officers’ (CEOs’) experiences occurring outside the work domain influence the performance of their respective firms. We suggest that the family-to-work conflict (FWC) that CEOs experience depletes their ability to self-regulate, thereby reducing their ability to make appropriately comprehensive decisions for their firms. This reduced decision-making comprehensiveness, in turn, has negative implications for firm performance. We further propose that CEOs’ levels of job engagement, or the extent to which they invest themselves in their work, can expand their capacity to withstand the negative effects of self-regulatory depletion. We test our hypotheses using a sample of 98 CEOs from the United States computer software and hardware industry. Findings confirm that reduced decision-making comprehensiveness represents one mechanism by which the experience of FWC in CEOs harms the performance of their firms. Moreover, CEO job engagement buffers both the negative effect of CEO FWC on decision-making comprehensiveness and the strength of the indirect relationship between FWC and firm performance via decision-making comprehensiveness.